Baby Incubator exhibit, Pay Streak, Alaska Yukon Pacific Exposiition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
PH Coll 727.655 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number